2022
DOI: 10.1177/11786302221120784
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Hand-Washing Practices at Critical Times Among Mothers of Under-5 Years Old Children in Rural Setting of Gedeo Zone, Southern Ethiopia

Abstract: Background: Various communicable and infectious diseases could be contained by proper hand washing leading to a reduction in mortality and morbidity of children. Objective: To assess predictors of hand-washing practices at critical times among mothers of under 5 years old children in rural setting of Gedeo zone, Southern Ethiopia. Method: An institutional-based cross-sectional survey was conducted among 422 women with children under the age of 5 attended the Dilla Zuria health facility and were chosen using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
2
3
0
Order By: Relevance
“…The findings indicated that only 42.2% of the mothers had good handwashing practices (95% CI: 37.5-46.9%). This is consistent with findings obtained from Northwest Ethiopia (39.1%) (Taddese et al 2020), rural areas of the Gedeo zone (44.9%) (Agaro et al 2022), and Woldia town in northeastern Ethiopia (46.5%) (Getahun & Adane 2021). The result is lower than other findings obtained from Debark town (52.2%) (Dagne et al 2019) and Kolladiba town, Northwest Ethiopia (51.2%) (Wolde et al 2022a(Wolde et al , 2022b.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings indicated that only 42.2% of the mothers had good handwashing practices (95% CI: 37.5-46.9%). This is consistent with findings obtained from Northwest Ethiopia (39.1%) (Taddese et al 2020), rural areas of the Gedeo zone (44.9%) (Agaro et al 2022), and Woldia town in northeastern Ethiopia (46.5%) (Getahun & Adane 2021). The result is lower than other findings obtained from Debark town (52.2%) (Dagne et al 2019) and Kolladiba town, Northwest Ethiopia (51.2%) (Wolde et al 2022a(Wolde et al , 2022b.…”
Section: Discussionsupporting
confidence: 92%
“…Then, a value of 1 was given for correct answers, and a value of 0 for incorrect or do not know responses. Households who scored above the mean knowledge score were considered as having good knowledge (Asekun-Olarinmoye Esther et al 2014;Agaro et al 2022). The attitude was assessed using seven questions on a Likert-type scale (Cronbach's alpha 0.75).…”
Section: Data Collection Tools Methods and Quality Assurancementioning
confidence: 99%
“…The proportion of mothers who practice hand washing with water and soap during critical times ranged from 33% before meals and to 12.6% after visiting the toilet. The finding is slightly similar with the study done in Gedeo zone, Ethiopia which shows 32.4% and 28.7% of mothers usually wash their hands before meals and after defecation [ 25 ]. In contrast, the finding is lower than the study conducted in Gondar, Northwest Ethiopia, which shows 86.3% and 64.9% of the mothers wash their hands before meals and after visiting the toilet, respectively [ 22 ].…”
Section: Discussionsupporting
confidence: 88%
“…Diarrhea, on the other hand, is a highly preventable disease that can be avoided by having adequate water, practicing proper sanitation, and hygiene practices. For example, studies have shown that hand washing with soap at critical moments can save one out of every three diarrhea-related deaths [7][8][9][10]. However, despite of even the COVID-19 pandemic putting a spot light on the importance of WASH, Worldwide, 2.2 billion people still lack access to safe drinking water.…”
Section: Introductionmentioning
confidence: 99%